Koutecky-Levich analysis applied to nanoparticle modified rotating disk electrodes: Electrocatalysis or misinterpretation? - Masa, J; Batchelor-McAuley, C; Schuhmann, W; Compton, R (2014)
The application of naive Koutecky-Levich analysis to micro- and nano-particle modified rotating disk electrodes of partially covered and non-planar geometry is critically analysed. Assuming strong overlap of the diffusion fields of the particles such that transport to the entire surface is time-independent and one-dimensional, the observed voltammetric response reflects an apparent electrochemical rate constant kapp o, equal to the true rate constant k o describing the redox reaction of interest on the surface of the nanoparticles and the ratio, ψ, of the total electroactive surface area to the geometric area of the rotating disk surface. It is demonstrated that Koutecky-Levich analysis is applicable and yields the expected plots of I -1 versus ω -1 where I is the current and ω is the rotation speed but that the values of the electrochemical rate constants inferred are thereof kapp o, not k o. Thus, for ψ > 1 apparent electrocatalysis might be naively but wrongly inferred whereas for ψ < 1 the deduced electrochemical rate constant will be less than k o. Moreover, the effect of ψ on the observed rotating disk electrode voltammograms is significant, signalling the need for care in the overly simplistic application of Koutecky-Levich analysis to modified rotating electrodes, as is commonly applied for example in the analysis of possible oxygen reduction catalysts. [Figure not available: see fulltext.] © 2014 Tsinghua University Press and Springer-Verlag Berlin Heidelberg.